1999
DOI: 10.1177/089443939901700302
|View full text |Cite
|
Sign up to set email alerts
|

Anthropology

Abstract: Five key problems of kinship networks are boundedness, cohesion, size and cohesive relinking, types of relations and relinking, and groups or roles. Approaches to solving these problems include formats available for electronic storage of genealogical data and representations of genealogies using graphs. P-graphs represent couples and uncoupled children as vertices, whereas parent-child links are the arcs connecting nodes both within and between different nuclear families. Using results from graph theory, P-gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(5 citation statements)
references
References 17 publications
0
3
0
2
Order By: Relevance
“…Also in social networks the application of graph theory is direct, as described in Kolomeets et al (2019). Even in the areas such as anthropology, graph theory is applied, as White et al (1999), where graphs are used to show marriage networks, for example. More obvious are the parallels between graph theory and geography, so there are even more studies to be found in the field of geography, from Pitts (1965) to Heckmann et al (2015).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Also in social networks the application of graph theory is direct, as described in Kolomeets et al (2019). Even in the areas such as anthropology, graph theory is applied, as White et al (1999), where graphs are used to show marriage networks, for example. More obvious are the parallels between graph theory and geography, so there are even more studies to be found in the field of geography, from Pitts (1965) to Heckmann et al (2015).…”
Section: Related Workmentioning
confidence: 99%
“…(2019). Even in the areas such as anthropology, graph theory is applied, as White et al . (1999), where graphs are used to show marriage networks, for example.…”
Section: Related Workmentioning
confidence: 99%
“…O uso de ferramentas computacionais para a descrição e a análise de sistemas de parentesco é uma metodologia amplamente documentada (Hamberger, 2011;Hamberger et al, 2009Hamberger et al, , 2014Héritier, 1981;White et al, 1999). Métodos informatizados vêm sendo usados por pesquisadores brasileiros há algum tempo, tendo como base a MaqPar ('Máquina do Parentesco'), um software desenvolvido por Marcio Silva e João Dal Poz com a finalidade de identificar e classificar os vários tipos de anéis matrimoniais existentes em uma rede genealógica (Bueno, 2015;Dal Poz & Silva, 2008, 2009Ferreira et al, 2014;Pires, 2009;Ramires, 2015;Silva, 2004Silva, , 2016Silva, , 2017.…”
Section: Materiais E Métodosunclassified
“…The GSC follows the graph theory definition [62] and contains metabolites that have routes (can be several) connecting them to each other; it is the most important subnet in the bow-tie structure.…”
Section: Similar Conceptsmentioning
confidence: 99%